Students Challenges in Learning Speaking Using E-Portfolio - Ali, Raden Muhammad; Affan, Dhava Chairul; Hastuti, Dwi; Azhari, Ahmad; Biddinika, Muhammad Kunta (English Teaching and Linguistics Journal (ETLiJ), 2024)
E-portfolio is one of the learning tools that has been applied for learning speaking at higher education. Although researchers and educators agree that e-portfolio has great potential and many advantages as assessment and learning tools, its implementation in the teaching and learning process is not as easy as expected. The evaluation of its implementation is urgently needed. This study aims to investigate university students’ challengess in learning speaking using e-portfolio. This research applies a descriptive qualitative method. The subjects of this research are the fifth semester students of the class of Public Speaking in the Academic Year of 2022/2023. Data was collected through observation, interview, and documentation. The data analysis technique is based on the theory of Matthew B Miles which includes: data reduction, data display, and conclusion drawing/verification.The result shows that students who participated in the class of Public Speaking which applies e-portfolio experienced several challenges, such as they: 1) are sometimes reluctant and lack of motivation, 2) are required to have a stable internet connection, 3) need some adaptations to develop e-portfolio as new learning tool,4) are required to have some ideas and creativities